New records of jejenes on the subgenus Stilobezzia of Stilobezzia (Diptera: Ceratopogonidae) from the Neotropical Region - Cazorla, Carla Gisela (2016)
Fil: Cazorla, Carla Gisela. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Entomología; Argentina